VÁZQUEZ GARCÍA, Francisco (2021). Cómo hacer cosas con Foucault. Instrucciones de uso, Madrid: Dado Ediciones, 238 pp. - Seoane Cegarra, José Benito (Daimon Revista Internacional de Filosofia, 2023)
Reseña sobre el libro VÁZQUEZ GARCÍA, Francisco (2021). Cómo hacer cosas con Foucault. Instrucciones de uso, Madrid: Dado Ediciones, 238 pp.